Pengaruh Progressive Muscle Relaxation terhadap Kualitas Tidur dan Kelelahan dalam Kegiatan Perkuliahan pada Mahasiswa Jurusan Okupasi Terapi Poltekkes Kemenkes Surakarta - Rina Kurnia; Lis Sarwi Hastuti (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background. Learning or lecturing is a process of interaction between instructors/teachers/lecturers and students. To obtain better learning outcomes, the learning approach used by lecturers influences students' activities and learning outcomes. The lecture process which involves physical and mental activity can cause learning fatigue and poor sleep quality. One effort that can be made to reduce study fatigue and improve student sleep quality is by providing progressive muscle relaxation (PMR) regularly. Objective. This study aims to determine the effect of PMR on sleep quality and fatigue during lecture activities among students majoring in Occupational Therapy, Health Polytechnic, Ministry of Health, Surakarta. Method. The design of this research is quasi experimental "One group pre and post test design with control group". Sampling was carried out using quota sampling technique. Sleep quality complaint data was taken using the Pittsburgh Sleep Quality Index (PSQI) instrument and fatigue data was taken using a subjective fatigue questionnaire. Results. Based on the independent sample T test statistical test, the results obtained for both sleep quality and fatigue variables showed significant differences in the intervention group compared to the control group, with P values ​​of 0.004 and 0.009 (P<0.05), respectively. Conclusion. Progressive Muscle Relaxation intervention affects sleep quality and fatigue during lecture activities in students of the Department of Occupational Therapy, Health Polytechnic, Ministry of Health, Surakarta. Keywords : Aerobic Low Impact, Stretching Exercise, Sleep Quality, Fatigue.